Role Of The Elderly In Bamboo Handcraft Production In Households At Bumi Subur Village Katingan Kuala Sub-District Katingan Regency - Lestari, Ulva Ayu; Safitri, Novi Angga; Jaki, Akhmad (AL-QARDH, 2024)
The research background is low in a family economy, so older people still have an important role in fulfilling their life needs, with a very low economy, they need help funding their daily lives. The objectives are to know the process of handcraft making by older people, the role of older people in bamboo handcraft marketing, and the older people's motivation in bamboo handcraft making in Bumi Subur Village. This research used field research with descriptive qualitative. Then, the subjects were the people who were active in bamboo handcraft production at Bumi Subur Village Katingan Kuala Sub-district Katingan Regency, older people, and their workplaces had permission. The sampling technique used purposive sampling. Data resources were obtained from interviews, observation and documentation. Data validation used triangulation technique, source triangulation and theory triangulation.The results showed that: the first process in handcraft making by older people was cutting the bamboo tree, bamboo stem can not be used directly, after that, rest it for 2-3 days. The measurement has been set to become an ingredient that is ready for plaited. the role of older people in bamboo handcraft marketing was to introduce the product directly to consumers and promote the product door to door, Pagatan market and Katingan market. the older people's motivation in making bamboo handcraft got additional income, so in elder time, they didn't just keep silence at home but were more productive with reason as a hobby and other.